2020
DOI: 10.1177/1524838020942754
|View full text |Cite
|
Sign up to set email alerts
|

Pornography and Sexual Aggression: Can Meta-Analysis Find a Link?

Abstract: Whether pornography contributes to sexual aggression in real life has been the subject of dozens of studies over multiple decades. Nevertheless, scholars have not come to a consensus about whether effects are real. The current meta-analysis examined experimental, correlational, and population studies of the pornography/sexual aggression link dating back from the 1970s to the current time. Methodological weaknesses were very common in this field of research. Nonetheless, evidence did not suggest that nonviolent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 71 publications
3
37
0
5
Order By: Relevance
“…In some cases, links between pornography use and negative couple outcomes (e.g., relational dissatisfaction) are reduced to statistical insignificance once other relevant factors (e.g., solo masturbation, religious prohibitions on pornography) are controlled (Perry, 2020). Similarly, some studies have found contradictory links between pornography use and aggression, calling into question prior positive associations between the two domains (Ferguson & Hartley, 2020). In keeping with our spectrum model of pornography effects, we suggest that links between pornography use and sexual satisfaction can range from positive to negative, depending on the context of the use.…”
Section: Pornography Use and Romantic Relationshipsmentioning
confidence: 99%
“…In some cases, links between pornography use and negative couple outcomes (e.g., relational dissatisfaction) are reduced to statistical insignificance once other relevant factors (e.g., solo masturbation, religious prohibitions on pornography) are controlled (Perry, 2020). Similarly, some studies have found contradictory links between pornography use and aggression, calling into question prior positive associations between the two domains (Ferguson & Hartley, 2020). In keeping with our spectrum model of pornography effects, we suggest that links between pornography use and sexual satisfaction can range from positive to negative, depending on the context of the use.…”
Section: Pornography Use and Romantic Relationshipsmentioning
confidence: 99%
“…Also, a recent meta-analysis found that violent and non-violent pornography is weakly correlated with sexual aggression. 19 This review is the first to summarize pornography addiction and sexual violence against women in India, indicating a research gap in the field exploring the variables. Additionally, due to limited studies that focus on the topic, further research in this field is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a recent meta-analysis found that violent and non-violent pornography is weakly correlated with sexual aggression. 19…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a direct association between pornography realism and sexual victimization is qualified by significant indirect associations in line with our theoretical reasoning, as discussed below. The meta-analytic conclusion by Ferguson et al [ 20 ] that evidence for a link between pornography use and sexual aggression is weak needs to be evaluated including evidence of indirect effect via sexual scripts, sexual behavior and sexuality-related attitudes referring to consensual sexual interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, significant longitudinal associations of frequency of pornography use with sexual victimization were found in different countries (e.g., [ 17 , 18 , 19 ]). Although support for a direct link between pornography use and sexual aggression perpetration has been questioned by a recent meta-analysis [ 20 ] and longitudinal studies from Croatia [ 21 , 22 ], other longitudinal studies have shown pornography use to be a moderator magnifying the link with other risk factors [ 23 ], or showing indirect associations via sexuality-related cognitions or behaviors [ 19 ].…”
Section: Introductionmentioning
confidence: 99%